2007
DOI: 10.1016/j.jaap.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of products from the pyrolysis of plastics recovered from the commercial scale recycling of waste electrical and electronic equipment

Abstract: Three plastic fractions from a commercial waste electrical and electronic equipment (WEEE) processing plant were collected and investigated for the possibility of recycling them by batch pyrolysis. The first plastic was from equipment containing cathode ray tubes (CRTs), the second plastic was from refrigeration equipment, and the third plastic was from mixed WEEE. Initially, the decomposition of each of the plastics was investigated using a TGA linked to a FT-ir spectrometer which showed that the CRT plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 24 publications
3
46
0
1
Order By: Relevance
“…Pyrolysis has been suggested to be a promising processing path for the treatment of WEEE plastics, but generates an oil with a high content of bromine, derived from the brominated flame retardants added to the plastic [4][5][6]. Zeolite catalysts have been used to reduce the amount of bromine in the product pyrolysis oil [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis has been suggested to be a promising processing path for the treatment of WEEE plastics, but generates an oil with a high content of bromine, derived from the brominated flame retardants added to the plastic [4][5][6]. Zeolite catalysts have been used to reduce the amount of bromine in the product pyrolysis oil [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant amount of research into the pyrolysis of PCBs has been reported, most of the work has been carried out under nitrogen atmosphere using analytical pyrolysis techniques or laboratory scale reactors involving measurement of kinetics [12][13][14][15] and characterization of its products obtained [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of BFRs and OPFRs in e-plastics has typically been performed using analytical techniques that involve physical sample preparation by grinding/chopping etc., solvent extraction and cleanup, and extract analysis with gas chromatography-mass spectrometry (GC-MS) [38][39][40][41][42] or liquid chromatography-mass spectrometry (LC-MS) [43][44][45][46][47]. More recently, the use of other methods including X-ray fluorescence (XRF) [48][49][50], Raman spectroscopy [50], Ion beam analysis (IBA) [51,52], and thermal analytical methods such as thermal desorption GC-MS have been proposed for FR analysis [39,[53][54][55].…”
Section: Analysis Of E-plasticsmentioning
confidence: 99%